Replacement of in vivo human rabies vaccine potency testing by in vitro glycoprotein quantification using ELISA – Results of an international collaborative study. Issue 6 (7th February 2017) - Morgeaux, Sylvie; Poirier, Bertrand; Ragan, C. Ian; Wilkinson, Dianna; Arabin, Ulrich; Guinet-Morlot, Françoise; Levis, Robin; Meyer, Heidi; Riou, Patrice; Shaid, Shahjahan; Volokhov, Dmitriy; Tordo, Noël; et al.
Highlights: Evaluation of 3 different ELISAs for quantifying human rabies glycoprotein. International study by 5 laboratories. Selection of one ELISA for proposal to EDQM for an international collaborative study. Abstract: Three different ELISAs quantifying rabies glycoprotein were evaluated as in vitro alternatives to the National Institutes of Health (NIH) in vivo potency test for batch release of human rabies vaccines. The evaluation was carried out as an international collaborative study supported by the European Partnership for Alternatives to Animal Testing (EPAA). This pre-validation study, the results of which are presented in this paper, compared three different ELISA designs, assessing their within- and between-laboratory precision. One of the ELISA designs was proposed to the European Directorate for the Quality of Medicines & HealthCare (EDQM) and accepted for an international collaborative study under the umbrella of the Biological Standardisation Programme.